Cumin wilt management – a review - R Mawar, S Lodha, (Journal of Spices and Aromatic Crops, 2014)
Cumin (Cuminum cyminum L.) is one of the oldest seed spice and an important production constraint is wilt caused by Fusarium oxysporum f. sp. cumini Prasad and Patel (Foc) and crop losses could be up to 60%. Maximum population of Foc was estimated at 0-5 cm soil depth in the presence of crop, but the population density tended to decline progressively with distance from the surface. Resting structures of the Foc, the chlamydospores, survive in the soil for more than 10 years. The inoculum density in the soil increases with each year of cumin cultivation and is directly proportional to disease incidence in the field. In this review, an effort has been made to compile research findings generated during past four decades on symptomatology, ecology and management strategies. In the absence of resistant sources against Foc, to reduce population of pathogen below the economic threshold level, integration of cultural, chemical and biological control measures is the only effective way to manage this diesease.